أثر برنامج تدريبي للمراقبة الذاتية في علاج مشكلة الانتباه لدى طلاب المرحلة الأساسية في مدينة سكاكا - الشديفات، محمود راشد (رابطة التربويين العرب, 2012)
هدفت هذه الدراسة إلى معرفة أثر برنامج تدريبي للمراقبة الذاتية في علاج مشكلة الانتباه لدى طلاب المرحلة الأساسية في مدينة سكاكا من خلال الإجابة على سؤال الدراسة "هل توجد فروق دالة إحصائياً عند مستوى الدلالة α=05.0 بين متوسطات سلوكات عدم الانتباه لدى الطلاب في مدارس مدينة سكاكا تعزي لمتغيري الدراسة: التدريب، الفئة العمرية والتفاعل بينهما؟" حيث تكونت عينة الدراسة من (56) طالباً ذكراً في فئتين عمريتين وهم الطلاب الذين حصلوا على العلامة المقطعية بعد الاست، ثم تم تقسيم أفراد العينة حسب متغيري الدراسة المجموعة والفئة العمرية- حيث اعتبر الطلاب في المرحلة الأساسية الأولى من 7- 9 سنوات الفئة العمرية الأولى في الصفوف (الأول والثاني والثالث) ومن 10- 12 سنة الفئة العمرية الثانية في الصفوف (الرابع والخامس والسادس). \ استخدام الباحث مقياس كونرز في صورته المعربة في هذه الدراسة وبالعلامة (55) على المقياس كنقطة قطع لاعتبار الطفل يعاني من قصور في الانتباه. كما اعتبر أن المراقبة الذاتية هي مجموعة الأفعال التي يقوم فيها الطفل لأداء النتاجات التالية: (التركيز على الهدف، سماع المنبه، الحفاظ على تسلسل العمليات، تسجيل عملية البقاء على المهمة، معرفة متى يتحقق الهدف، معرفة متي يتم الانتقال إلى العمليات التالية، اختيار العملية الملائمة التي تتبع في السياق، اكتشاف العقبات والأخطاء)، ويتحدد مستوى الانتباه بمستوى الأداء بالملاحظة التي تكشف عن عناصر أساسية في الانتباه من مثل التركيز والانتقاء الموجه لخصائص المثير والانتباه، والاستماع للمنبه، ثم قام الباحث بتطبيق البرنامج في خمسة أسابيع، من خلال (12) جلسة تدريبية. وقد كانت مدة الجلسة (30) دقيقة. تم تطبيقها في حصص اللغة العربية والعلوم لكل الصف. \ وقد أظهرت نتائج الدراسة وجود فروق ظاهرية بين المتوسطات الحسابية لسلوكات عدم الانتباه لدى الطلاب في مدارس مدينة سكاكا للاستجابة البعدية ناتج عن اختلاف مستويي متغيري الدراسة (التدريب، الفئة العمرية)، كما أظهرت النتائج وجود فرق لصالح أفراد المجموعة التجريبية الذين درَّبوا على المراقبة الذاتية للانتباه باستخدام البرنامج التدريبي مقارنة بنظرائهم من أفراد المجموعة الضابطة الذين لم يدرُّبوا على البرنامج التدريبي، وقد أوصى الباحث ببناء برنامج عربي مقنن لمعالجة مشكلة قصور الانتباه كما أوصى الباحث تعريف الطلبة بمشكلاتهم الأساسية التي تسبب لهم قصور الانتباه. The aim of this study was to investigate the impact of a training program for self-monitoring in the treatment of the problem of attention among students in basic stage in the city of Sakaka through the stud)' to answer the question "Are there any differences statistically significant at the significance level a = 0,05 between the averages of inattention behaviors among students in schools City Sakaka attributed to the variables of the study: training, age group, ana the interaction between them? The studv sample consisted of 56 male students in two age groups , the students who have received the mark after CT, and then the sample was divided according to the variables of the studv group and age group - where the students were considered in basic first phase of the 7-9 years age group first in rows (the first, second and third) and 10-12 years age group in the second rows (IV, V and VI). The researcher used a Connor's scale in its Arabized shape in this study and the mark (55) on the scale as the cut point to be considered the child suffers from a lack of attention. It was also considered that self¬monitoring is a group acts in which a child's performance outputs the following: (a focus on the goal, to hear the alarm clock, maintaining the sequence of operations, registration process to stay on task, knowing when to achieve the goal, knowing when you are going to the following operations, selection process appropriate that follow in context, the discovery of the obstacles and errors), and is determined by the level of attention to performance noting that reveal the essential elements in the attention of such focus and selection-oriented features exciting and attention, and listen for the alarm clock. Then the researcher applied the program in five weeks, through (12) training sessions. The session length was 30 minutes. They have been applied in the classes of the Arabic language and science for each grade The study results showed the existence of apparent differences between the arithmetical averages of behaviors, lack of attention of the students in the schools of the city of Sakaka response posteriori resulting from different levels of the variables of the study (training, age group). And the results showed a difference in favor of the experimental group who were trained in self-mohitoring of attention by using The training program compared with their counterparts from the members of the control group who were not trained on the training program. The researcher has recommended for building the Arabic codified program to treat the problem of attention deficit. Also, the researcher recommended for basic acquaint to introduce students with their problems that cause them attention deficit.
Keywords: سكاكا -- علم النفس المعرفي -- طلاب المدارس الأساسية -- البرامج التدريبية -- صعوبات التعلم -- التعلم الذاتي -- السعودية